Insights Into the Environmental Impact on Genetic Structure and Larval Dispersal of Crown-of-Thorns Starfish in the South China Sea - Chen, Biao; Yu, Kefu; Yao, Qiucui; Liao, Zhiheng; Qin, Zhenjun; Yu, Xiaopeng; Wu, Qian; He, Biao (Frontiers in Marine Science, 2021)
The coral-eating crown-of-thorns starfish (COTS; Acanthaster spp) is a major factor in coral reef degradation in the Indo-Pacific region. However, the environmental impact on phylogenetic and genetic characteristics of COTS in the northern Indo-Pacific convergence region remains unclear. We used mitochondrial DNA (mtDNA) and microsatellite markers to analyze the phylogenetic relationship, demographic history, genetic diversity and genetic structure of COTS in the South China Sea (SCS) and explored the environmental impact on historical population expansion, genetic differentiation and larval dispersal. Herein, there was a clear signature of a population expansion in the SCS using mtDNA marker. For microsatellite loci analysis, COTS have high genetic diversity in the SCS. STRUCTURE analysis indicated that COTS in the Pacific Ocean can be divided into four subgroups: the SCS, Western Pacific, Pacific equatorial current affected zone, and Pacific insular atolls populations in the Pacific Ocean. Fst-statistical analysis revealed that there are positive correlations between Fst values and geographic isolation for all sampling sites. Also, there are no obvious associations between Fst values and chlorophyll a concentrations among coral reefs in the SCS, but there are significant positive associations between Fst values and particulate organic carbon (POC) concentrations within small geographic distances. These results suggested that COTS underwent historical population expansion after the Last Glacial Maximum, possibly followed by coral population expansion. Genetic structure of COTS populations was possibly shaped by distinct nutrient concentration, especially different POC concentrations, over small geographic distances. Moreover, ocean currents provide a potential dispersal mechanism for COTS larvae in the SCS. This study highlights that environmental and oceanographic factors play important roles in shaping genetic characteristics and larval dispersal of COTS populations in northern Indo-Pacific convergence region.